Holy Bible. [compact disc, unabridged] Deuterocanonicals/Apocrypha: part 1. (Deuterocanonicals/Apocrypha, 2004)
Word-for-word unabridged recording of Tobit, Judith, Esther, Baruch, Letter of Jeremiah, song of the three Hebrews, Susanna, Bel and the Dragon, narrated in contemporary language for easy understanding.